DISTRIBUTED DEEP LEARNING MODELS FOR PRECISE WEED DETECTION IN CROP FIELDS - Hoshko, Bohdan; Stan’ko, Volodymyr (European Science, 2025)
This paper presents distributed deep learning models for accurate weed detection in agricultural crops such as wheat, soybean, corn, and potato.The study explores federated learning architectures combining ResNet50, U-Net++, Swin Transformer, and YOLOv8